NCMP-07. IDH MUTANT GLIOMAS PROMOTE EPILEPTOGENESIS VIA D-2-HYDROXYGLUTARATE DEPENDENT MTOR HYPER-ACTIVATION. (12th November 2021) - Mortazavi, Armin; Fayed, Islam; Bachani, Muzna; Dowdy, Tyrone; Jahanipour, Jahandar; Khan, Anas; Yang, Chungzhang; Maric, Dragan; Larion, Mioara; Ksendzovsky, Alexander; Zaghloul, Kareem
Abstract: Uncontrolled seizures in patients with low grade gliomas have a significant impact on quality of life and morbidity, yet the mechanisms through which these tumors cause seizures remain unknown. Albeit there are multiple features that contribute to tumor related epileptogenesis, IDH mutations are determined to be an independent factor, although the pathogenesis remains poorly understood. Here, we hypothesize that the active metabolite D-2-hydroxyglutarate (D-2-HG) produced by the IDH-mutant enzyme leads to metabolic disruptions in surrounding cortical neurons that consequently promote seizures. We use a complementary study of in vitro cortical cultures and electrographically sorted human cortical tissue from patients (n=5) with IDH-mutant gliomas to test this hypothesis. We demonstrate that D-2-HG leads to increased neuronal spiking activity (p< 0.0001) and promotes a distinct metabolic profile in surrounding neurons and upregulation of mTOR signaling (p< 0.0001), which is consistent in human epileptic cortex compared to peritumoral nonepileptic cortex. Furthermore, increases in neuronal activity are induced by mTOR activation and reversed with mTOR inhibition. Together, our data suggest that metabolic disruptions and mTOR signaling upregulation in the surrounding cortex due to D-2-HG may be a driving event for epileptogenesis in patients with IDH-mutant low grade gliomas.